Zeugma, Türkei: Untersuchungen an der römischen Stadtmauer von Zeugma (Seleukia am Euphrat) - Jonasch, Melanie (e-Forschungsberichte des DAI, 2023)
Between 2009 and 2012 investigations were conducted in the urban area of Seleucia/Zeugma on the Euphrates with the aim of locating the Hellenistic and Roman city walls. In 2012, a small section of the Roman wall in the east of the city was unearthed. The excavated remains consist of a curtain wall, 2.50 m wide, and a projecting tower added subsequently. However, the analysis of the pottery showed that both parts were built in the first half of the first century AD. The project thus provides the first evidence for the course, the appearance and date of the Roman urban defences on the qeastern side of the city.